From Physical Health Preservation to Cultural Identity: The Dissemination and Construction of Cross-cultural Body Practices in the "Chinese Medicine Fever" on the Internet - Zhang, Jiachang (International Journal of Social Sciences and Public Administration, 2026)
As a vivid carrier of excellent traditional Chinese culture, traditional Chinese medicine carries the Eastern wisdom of "unity of heaven and man", "dialectical treatment", and "prevention of disease". Its dissemination essence is a cross-cultural dialogue with the body as the medium and health preservation as the starting point. In recent years, the "Chinese medicine craze" on the extranet has continued to rise. Chinese medicine physical practices such as acupuncture and moxibustion, moxibustion, Chinese medicine conditioning, meridian massage, and dietotherapy regimen have gradually extended from the initial demand for "curing diseases and curing diseases" to an important path for overseas people to perceive Chinese medicine culture and identify with Chinese culture. This article is based on the core theory of traditional Chinese medicine, combined with typical cases of traditional Chinese medicine dissemination on the internet, to explore the dissemination path of traditional Chinese medicine body practice in cross-cultural contexts, analyze how body experience is transformed into cultural identity, reveal the role of traditional Chinese medicine body practice in constructing excellent traditional Chinese culture in cross-cultural dissemination, highlight the core concept and contemporary value of traditional Chinese medicine "people-oriented" and "conforming to nature", and provide a reflection on the combination of traditional Chinese medicine charm and practical significance for the overseas dissemination of traditional Chinese medicine culture.